2019
DOI: 10.1111/scs.12651
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals and volunteers education in palliative care to promote the best practice–an integrative review

Abstract: Background Family caregivers’ empowerment can assume strategic importance in palliative care. Healthcare professionals and volunteers have been showing significant gaps in this field. Hence, education has been advocated as an effective strategy to fill this gap. While several educational initiatives exist, a comprehensive evidence synthesis on the effectiveness of educational training on healthcare professionals and volunteers is lacking. Aims An integrative review was conducted to explore worldwide initiative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 42 publications
1
18
0
2
Order By: Relevance
“…Spirituality was the only context where nurses stated the need for competence in addressing different cultures. However, cultural care is defined as one of the core competence areas of palliative and EOL care (12,17) and is important when assessing the competence level and educational needs of nurses (18,19). This increases the challenge for quality care in organisations, as nurses have little experience and knowledge of how to consider different cultures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spirituality was the only context where nurses stated the need for competence in addressing different cultures. However, cultural care is defined as one of the core competence areas of palliative and EOL care (12,17) and is important when assessing the competence level and educational needs of nurses (18,19). This increases the challenge for quality care in organisations, as nurses have little experience and knowledge of how to consider different cultures.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, competence requires skills relating to cooperation and multiprofessionalism, in addition to continuous professional development. Same competence areas have been recognised to be essential when assessing nurses' knowledge, skills and educational needs (18,19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specialised education can improve nurses’ advanced assessment and care skills; poor education hinders appropriate EOL nursing care (Anstey, Powell, Coles, Hale, & Gould, ; Teixeira et al, ). Palliative care is lacking in nursing curricula (Paice et al, ); 75% of nurses working in Japanese EOL facilities for older adults reported never receiving EOL care education (Okumura‐Hiroshige et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies evaluated students' satisfaction before and after their education and attitudes towards patient care, knowledge, and behavioural changes (Anstey et al, ; Morita et al, ; Smith et al, ). However, the ELNEC‐JG's effectiveness has not been measured using reliable and valid scales (Kubota et al, ; Teixeira et al, ), and few studies have examined long‐term changes in outcomes (Anstey et al, ; Kunte, Johansen, & Isenberg‐Cohen, ). Many evaluations focused on students' satisfaction or intervention usefulness.…”
Section: Introductionmentioning
confidence: 99%